2022
DOI: 10.1021/acs.bioconjchem.2c00419
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Electrophilic Cysteine Arylation with Pyridinium Salts

Abstract: Here, we present a series of fluorinated cationic reagents that enable rapid arylation of cysteine under mild conditions compatible with proteins and peptides. The highly polarized C–F bond and attractive nucleophile–electrophile Coulombic interactions substantially accelerate cysteine arylation, leading to unusually high rate constants on the order of 100 M–1·s–1 and allowing for equimolar labeling of substrates at micromolar concentrations. The synthetic modularity of this approach promotes the direct coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Examples include cysteine arylation with electron-deficient aryl halides for the S N Ar reaction ( e.g. perfluoroarene, 8–10 fluorinated pyridinium salts, 11 and aryl thioethers 12 ) and activated arene species ( e.g. hypervalent iodine reagent 13 and diazo compounds 14,15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include cysteine arylation with electron-deficient aryl halides for the S N Ar reaction ( e.g. perfluoroarene, 8–10 fluorinated pyridinium salts, 11 and aryl thioethers 12 ) and activated arene species ( e.g. hypervalent iodine reagent 13 and diazo compounds 14,15 ).…”
Section: Introductionmentioning
confidence: 99%
“…4). 41 Furthermore, polarized double bonds have led to multiple Cys-selective bioconjugation reagents. The regulation of LUMO energy through electron-withdrawing groups or strain has been examined to tune reactivity and selectivity in such cases.…”
Section: Route Amentioning
confidence: 99%
“…Achieving a versatile reaction platform requires a good structural diversity and a thorough understanding of the structure–activity relationship (SAR), which by regulating the stability and cleavability of the bioconjugates and stapled peptides could enable fine-tuning of biological activity. Our group has recently investigated the unique reducibility and biophysical properties of positively charged compounds, such as sulfoniums and pyridiniums, making them promising candidates for bioconjugation. Aromatic nucleophilic substitute (S N Ar) reactions have been extensively researched and applied within the realm of bioconjugation chemistry, with reports showcasing the substantial potential of such reagents when employing nitrogen-containing heterocycles and their onium salts as conjugation reagents. Drawing on the in-depth understanding of these electron-deficient compounds, we identified that pyridiniums with halogen as a leaving group would be a suitable platform for tunable bioconjugation through the S N Ar. The electrophilicity of the halo-pyridiniums could be predicted and finely tuned by altering the effective nuclear charge, owing to the well-understood electron effects of substituents on aromatic rings .…”
Section: Introductionmentioning
confidence: 99%